EXPERIMENTS ON GREENLAND WHITEOUT MODIFICATION-1960 - JIUSTO,JAMES E.; ROGERS,R.R. (1961)
A 2-month experimental program was conducted in Greenland to determine the extent to which arctic whiteouts and low clouds could be modified using cloud dissipation techniques. Seven seedingAGENTS, APPLICABLE TO SUPERCOOLED OR WARMER-THANFREEZING CLOUDS, WERE TRIED EMPLOYING AIRCRAFT, TETHERED BLIMP-BALLOON, AND ROCKET DELIVERY. Successful dissipation of supercooled clouds was achieved with dry ice. As little as 5 lb of dry ice per mile, dispersed from aircraft, produced efficient clearing action and line openings up to 2.5 miles wide. An inexpensive seeding scheme, involving a tethered blimp-balloon and open baskets of dry ice attached at intervals along the tether line, was shown to be capable of opening holes in low cloud overcasts. Such a technique appears feasible for maintaining safe landing corridors at ice-cap airstrips during fog and low stratus conditions. Seeding materials that were ineffective in dissipating the supercooled clouds or warmer-than-freezing clouds encountered were liquid carbon dioxide, Greenland soil particles, silver iodide, carbon black, calcium chloride, and sodium chloride. Cloud hydrometeor and atmospheric nuclei measurements were made in relation to the modification tests. (Author)